Relapse in schizophrenia: Definitively not a bolt from the blue. (16th March 2018) - Spaniel, Filip; Bakstein, Eduard; Anyz, Jiri; Hlinka, Jaroslav; Sieger, Tomas; Hrdlicka, Jan; Görnerová, Natálie; Höschl, Cyril
Highlights: Early warning signs (EWS) of schizophrenia relapse were analyzed using a telemedicine system. Previous studies demonstrated symptom increase 2–4 weeks before relapse. Here, the onset of continuous changes in EWS occurred 2 months prior hospitalization. EWS precede relapse of schizophrenia much earlier than previously suggested. Abstract: Detailed study of the period before schizophrenic relapse when early warning signs (EWS) are present is crucial to effective pre-emptive strategies. To investigate the temporal properties of EWS self-reported weekly via a telemedicine system. EWS history was obtained for 61 relapses resulting in hospitalization involving 51 patients with schizophrenia. Up to 20 weeks of EWS history per case were evaluated using a non-parametric bootstrap test and generalized mixed-effects model to test the significance and homogeneity of the findings. A statistically significant increase in EWS sum score was detectable 5 weeks before hospitalization. However, analysis of EWS dynamics revealed a gradual, monotonic increase in EWS score across during the 8 weeks before a relapse. The findings—in contrast to earlier studies—suggest that relapse is preceded by a lengthy period during which pathophysiological processes unfold; these changes are reflected in subjective EWS.